Exploring Teachers' Strategies in Speaking Skill at the Tenth Grade Students of SMA Negeri 13 MBD - Perasoa, Angga Nita; Binnendyk, Sophia; Tiwery, Dian Sartin (Prodi Pendidikan Bahasa Inggris, Program Studi Diluar Kampus Utama (PSDKU) Unpatti-MBD, 2024)
This study investigates teachers’ strategies to enhance speaking skills among tenth-grade students at SMA Negeri 13 MBD. Using a qualitative approach that involved interviews and observations, the researcher focused on the experiences and classroom practices of the English teacher. The study identified four primary strategies utilized in teaching speaking: think pair share, role play, storytelling, and group discussion. Each technique fosters a supportive learning environment, encourages student interaction, and boosts confidence in speaking English. The findings indicate that these strategies improve students’ fluency and accuracy and engage them more deeply in the learning process